Molecular Review Covid19 from the Pathogenesis and Transmission Aspect - Fery Setiawan; Heni Puspitasari; Jenny Sunariani; Ahmad Yudianto (Universitas Airlangga, 2020)
Introduction: Corona disease-19 virus (COVID-19) spread and caused a pandemic that affected people all over the world. COVID-19 is also called Severe Acute Respiratory Syndrome-Coronavirus Disease (SARS-CoV). Discussion: COVID-19 is a β-coronavirus serotype which is a single strain of RNA virus and was an outbreak in 2002 (SARS-CoV) and 2012 (MERS-CoV). COVID-19 has Open Reading Frames (ORFs) consisting of Spikes (S), Envelopes (E), Membranes (M), and Nucleocapsids (N) with S parts being a glycoprotein that can attach to receptors owned by host cells, the receptors are CD 26, ACE-2, Ezrin, and Cyclophilins with the main receptor being ACE-2 in the lung organs. Process would evoke a host body's immune response consisting of natural and adaptive immune systems, involving the Antigen Presenting Cell (APC) system which consists of two, namely: Major Histocompatibility Complex (MHC) class I and II. APC could also generate adaptive immune system, consists of B and T cells. COVID-19 had the ability to survive in B and T cells, so that cytokine-chemokine secretion continues to be known as cytokine storm that trigger Acute Respiratory Distress Syndrome (ARDS) and death. Conclusion: The recovery prognosis of COVID-19 depended on the detection of COVID-19 patients because it was related to the severity of ARDS, so the earlier it was detected, the greater the chance of recovery.